Fourth Branch Agencies: A Silver Bullet for Making Government Accountable? - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2025)
A new consensus appears to have emerged among academics and policy practitioners: Governments can be made to respect constitutional rules by establishing and constitutionally entrenching watchdogs, such as anti-corruption commissions, electoral commissions, or ombudspersons. In this article, we evaluate the consequences of what we propose to call the New York Consensus. We find that fourth branch agencies can increase constitutional compliance, but their effects are largely limited to higher income countries with a democratic political system.
Keywords: 340; New York Consensus; fourth branch; integrity branch; guarantor branch; constitutional compliance; de jure-de facto gap; separation of powers